Where the body ends - Hardy, Stacy (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My collection of stories explores the intersection of the human body and the body of text via the tropes of disease and animality. Drawing on my experience of living with tuberculosis for many years, I attempt to write disease differently "“ not merely to be survived, overcome, cured, eradicated, but as something to be embraced via the Deleuzian affirmation of being worthy of what happens to us. Taking my cue from Sontag, I use a creaturely approach to writing, "an infinitely varied register of forms and tonalities for transporting the human voice into prose narrative" , emphasising the shared embodiedness of humans and animals so as to challenge the omnipotence of thought that subjugates and colonises the body as exclusively human.
Keywords: Uncatalogued